DISTANCE LEARNING AT UNIVERSITY - Tatiana N. Andryukhina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Modern higher education in Russia turns great attention on application in educational process of various technologies of information transfer. The priority direction for higher education institutions is creation and sovershenstvoany systems of distance learning of students. The technique of application of this form of education in Russia is supported by the approved normative legal acts and laws. The article presents an analysis of the differences distance learning from intramural and extramural mode of study. Presents the conditions for successful implementation of distance learning at university. Analyzed the characteristic features of distance learning. The experience of the application distance learning process in Samara State Technical University considered by the article. Electronic remote educational technologies are used in absentia training that allows to increase availability and quality of training of students. Now at faculty of remote and additional education training of students more than in thirty educational directions is conducted. The article presents a simplified structure of the organization of educational process.